Analisa Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Industri dan Penentuan Prioritas Layanan - Ratna Sari, Linda; Rahayu, Betty (eBA Journal: Journal Economics, Bussines and Accounting, 2016)
PLN East Java Business Unit is one of the service industry that has  important in his development as a service industry. PLN will understand their desires and create customer satisfaction according to expectations of the customers. To determine the variables that affect customer satisfaction PLN, the fit between customer perceptions and expectations PLN and variables that need to be prioritized are the objectives of this study. To answer that, the variables used in this study is covering variable customer profile, service attribute variables and variable prioritization of services. From the analysis of the industry grouping customers based on their level of satisfaction, then generally the customer on PT. Business Unit PLN Gresik is where sampling is not satisfied with the services they have rendered. It is seen from the gap value is still negative, this means that customers in each of the groups formed have higher expectations than reality service received.